PENGARUH KUALITAS KEHIDUPAN KERJA DAN SIKAP KERJA TERHADAP KEPUASAN KERJA GURU SMA NEGERI KECAMATAN JEKAN RAYA KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - Moh. Khoiri (Jurnal Ilmiah Mimbar Demokrasi, 2018)
This study aims to determine the effect of (1) the quality of work life, (2) working attitude, (3) job satisfaction of teachers working SMA Kecamtan Jekan Kingdom city of Palangkaraya , Central Kalimantan Province. In the data analysis, this study used a survey method using a causal analysis technique Strip . This study used a sample of 138 teachers in three high schools in District Jekan Kingdom city of Palangkaraya are selected using Slovin formula.The results showed that : first , there are positive influence between the quality of work life and job satisfaction of teachers in schools . Secondly , there is a positive effect between work attitudes and job satisfaction of teachers in schools . Third , there is a positive effect between the quality of working life and work attitudes of teachers in schools.